Oxide-doped hydrogen evolution electrocatalyst and preparation method and use thereof

By doping perovskite oxides and trace metal ions in traditional platinum carbon catalysts, proton conduction and catalytic activity in the hydrogen evolution reaction are improved, and the problems of high cost and insufficient durability of traditional catalysts are solved, and a more efficient and durable electrolytic hydrogen production catalyst is achieved.

CN115386907BActive Publication Date: 2025-04-25NANJING TECH UNIV

Patent Information

Application Number
CN202210998666.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-19
Publication Date
2025-04-25
Estimated Expiration
2042-08-19

AI Technical Summary

Technical Problem

The traditional hydrogen evolution reaction catalyst has high cost and insufficient durability, which hinders the industrialization development of hydrogen production by electrolyzing water.

Method used

Perovskite doping method is used to dopate perovskite oxides with proton conduction capabilities in a carbon substrate with high specific surface area to improve the proton conduction process in the hydrogen evolution reaction, and dopant modification of ruthenium through the precipitation of trace metal ions to improve the activity and durability of the catalyst.

Benefits of technology

It significantly improves the activity of Ru during catalytic hydrogen evolution, extends the durability of the catalyst, reduces the influence of carbon corrosion, and improves the performance under the actual hydrogen production conditions of hydrogen production by electrolyzing water in the proton exchange membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003806658780000091
    Figure BDA0003806658780000091
  • Figure BDA0003806658780000101
    Figure BDA0003806658780000101
  • Figure HDA0003806658790000011
    Figure HDA0003806658790000011
Patent Text Reader

Abstract

The invention relates to a hydrogen evolution catalyst doped with a perovskite material and a preparation method thereof. The catalyst is composited with a perovskite material having a certain proton conduction ability and high specific surface area carbon as a substrate and monodispersed noble metal nanoparticles loaded thereon. The catalyst is characterized in that the doped perovskite material enhances the conduction of protons in a hydrogen evolution reaction and substrate stability, the uniformly dispersed nano-ruthenium particles loaded thereon are the main active sites, the perovskite material can enhance the proton conduction in the rate-controlling step of the hydrogen evolution reaction, and greatly improves the hydrogen evolution performance of the catalyst, and has good application prospects in the field of hydrogen production by proton exchange membrane water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a perovskite material-doped hydrogen evolution catalyst and a preparation method thereof, and belongs to the technical field of proton exchange membrane water electrolysis hydrogen production catalysts. Background Art

[0002] Proton exchange membrane water electrolysis uses perfluorosulfonic acid proton exchange membrane with good chemical stability, proton conductivity and gas separation as solid electrolyte, which can effectively prevent electron transfer and improve the safety of electrolyzer. Compared with alkaline water electrolysis, proton exchange membrane water electrolysis has a higher working current density (>1A / cm 2 ), with higher overall efficiency (74% to 87%), higher hydrogen gas volume fraction (>99.99%), higher gas production pressure (3 to 4 MPa), faster dynamic response speed, and the ability to adapt to the volatility of renewable energy generation. It is considered to be a water electrolysis hydrogen production technology with great development prospects. At present, proton exchange membrane water electrolysis hydrogen production technology has been demonstrated and applied in the fields of hydrogen production at hydrogen refueling stations, wind power and other renewable energy water electrolysis hydrogen production, energy storage, etc., and has been gradually promoted.

[0003] As we all know, the biggest problem of cathode catalysts in proton exchange membrane water electrolysis is high cost and low stability. Precious metal platinum-based catalysts are currently recognized as the catalysts with the highest activity in hydrogen evolution reaction, but the reserves of platinum are small and the platinum loading requirement on the cathode hydrogen evolution reaction side is high. While people use a large amount of platinum, the cost of proton exchange membrane water electrolysis for hydrogen production has increased. However, once the platinum loading is reduced, the activity and durability of the catalyst will also decrease. Pt / C catalysts are still commonly used in industrialization. Although they are highly mature, in addition to the cost problem, the durability of the catalyst itself is still a key issue hindering the development of proton exchange membrane water electrolysis for hydrogen production catalysts. Traditional platinum-carbon catalysts are metal platinum loaded on some ordinary carbon substrates with only a certain specific surface area. The carbon material itself has only inherent electron conduction ability and has almost no promoting effect on the hydrogen evolution reaction. In addition, carbon corrosion will reduce the durability of the substrate. High platinum loading also exacerbates the cost problem. Therefore, the key issue in the development of cathode hydrogen evolution reaction catalysts in proton exchange membrane water electrolysis to produce hydrogen is how to reduce costs while improving durability and designing catalysts that are more suitable for industrialization. Summary of the invention

[0004] The technical problem to be solved by the present invention is that the traditional platinum-carbon catalyst for hydrogen evolution reaction is high in cost and lacks durability, which hinders the industrial development of hydrogen production by water electrolysis. The traditional carbon substrate itself only has conductive properties and has almost no promoting effect on the surface metal active sites. The metal particles loaded thereon are often easy to agglomerate.

[0005] In the technical solution of the present invention, a perovskite doping method is adopted to dope a stable perovskite oxide with proton conductivity into a traditional high specific surface area carbon substrate, thereby improving the proton conduction process in the rate-controlling step of the hydrogen evolution reaction; at the same time, trace metal ions can be precipitated from the perovskite during preparation, and then the doping modification of ruthenium at the main active site can be achieved, which can improve the intrinsic activity of the catalyst; at the same time, the doping of perovskite can inhibit the agglomeration of metal particles on the surface of the substrate, improve the interaction between the metal and the carrier, reduce the impact of carbon corrosion, and improve the durability of proton exchange membrane water electrolysis under actual hydrogen production conditions.

[0006] The specific technical solution is:

[0007] A hydride-doped hydrogen evolution electrocatalyst comprises a substrate and Ru nanoparticles loaded on the substrate; the substrate is a mixture of a carbon material and a perovskite oxide, and the perovskite oxide is selected from BaZr 0.1+x Ce 0.8-z- y Y 0.1+y O 3-σ , and the Ru nanoparticles are also doped with metal elements Ba and Ce, 0.1≤x,y≤0.1.

[0008] The particle size of the Ru nanoparticles is 3-5 nm.

[0009] A method for preparing a hydride-doped hydrogen evolution electrocatalyst comprises the following steps:

[0010] Step 1, mixing perovskite oxide and carbon particles and dispersing them in a first solvent, and drying them to obtain a composite carrier;

[0011] Step 2, dissolving the composite carrier and the ruthenium source in a second solvent, adding a reducing agent to carry out a reduction reaction so that ruthenium is loaded on the composite carrier, and separating and drying the product to obtain a catalyst.

[0012] In the step 1, the weight ratio of perovskite oxide to carbon particles is 1:0.5-1.5.

[0013] In the step 1, the perovskite oxide is prepared by a sol-gel method.

[0014] In the step 2, the reducing agent is sodium borohydride.

[0015] In the step 2, the reducing agent is first dispersed in the second solvent and then slowly added to carry out the reduction reaction.

[0016] In the step 2, the weight ratio of the composite carrier, the ruthenium source and the reducing agent is 1:0.5-1.5:1-3.

[0017] In the step 2, the reaction conditions are 20-60° for 5-15h.

[0018] Application of hydride-doped hydrogen evolution electrocatalysts in hydrogen production via proton exchange membrane water electrolysis.

[0019] A method for doping Ba and Ce in a ruthenium catalyst comprises the following steps:

[0020] Step 1: Perovskite oxide BaZr 0.1+x Ce 0.8-z-y Y 0.1+y O 3-σ Mixing with carbon particles and dispersing in a first solvent, and drying to obtain a composite carrier;

[0021] Step 2, dissolving the composite carrier and the ruthenium source in a second solvent, adding a reducing agent to carry out a reduction reaction, so that ruthenium is loaded on the composite carrier, and part of the Ba and Ce in the perovskite oxide is reduced and precipitated to be doped into the ruthenium nanoparticles.

[0022] Beneficial Effects

[0023] The advantages of the present invention are: a perovskite doping method is adopted to dope a stable perovskite oxide with proton conductivity in a traditional high specific surface area carbon substrate, thereby improving the proton conduction process in the hydrogen evolution reaction, which can significantly improve the activity of Ru in catalyzing hydrogen evolution;

[0024] In addition, the perovskite oxide can also precipitate a portion of its own trace metal ions during the reduction reaction of Ru, achieving the doping modification of ruthenium at the main active site, further improving the activity of the catalyst;

[0025] At the same time, the doping of perovskite can inhibit the agglomeration of metal particles on the substrate surface, improve the interaction between the metal and the carrier, reduce the impact of carbon corrosion, and improve the durability of proton exchange membrane water electrolysis under actual hydrogen production conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The mixed substrate BaZr prepared in Example 1 0.1 Ce 0.7 Y 0.2 O 3-σ -C sandwich experiment diagram.

[0027] Figure 2 The Ru-BaZr prepared in Example 1 0.1 Ce 0.7 Y 0.2 O 3-σ -SEM image, spherical aberration electron microscope image and TEM image of C.

[0028] Figure 3 The Ru-BaZr prepared in Example 1 0.1 Ce 0.7 Y 0.2 O 3-σ XRD and XPS patterns of -C catalyst.

[0029] Figure 4 The Ru-BaZr prepared in Example 1 0.1 Ce 0.7 Y 0.2 O 3-σ -Comparison of LSV performance between C and commercial platinum-carbon catalysts.

[0030] Figure 5 The Ru-BaZr prepared in Example 1 0.1 Ce 0.7 Y 0.2 O 3-σ -C and commercial platinum-carbon catalyst performance comparison of water electrolysis hydrogen production devices.

[0031] Figure 6 The Ru-BaZr prepared in Example 1 0.1 Ce 0.7 Y 0.2 O 3-σ -C TEM image after electrochemical stability test.

[0032] Figure 7 The Ru-BaZr prepared in Example 1 0.1 Ce 0.7 Y 0.2 O 3-σ Comparison curve of electrochemical stability between -C and commercial platinum carbon.

[0033] Figure 8 The Ru-BaZr prepared in Example 2 0.1 Ce 0.8 Y 0.1 O 3-σ -C and commercial platinum-carbon catalyst electrochemical performance comparison curve.

[0034] Fig. 9 The Ru-BaZr prepared in Example 3 0.2 Ce 0.7 Y 0.1 O 3-σ -C and commercial platinum-carbon catalyst electrochemical galvanostatic stability curves.

[0035] Fig.10 The Ru-BaZr prepared in Example 4 0.2 Ce 0.6 Y 0.2 O3-σ -C and commercial platinum-carbon catalyst stability comparison curve of water electrolysis hydrogen production device.

[0036] Fig.11 The Ru-BaZr prepared in Example 5 0.1 Ce 0.6 Y 0.3 O 3-σ -C and commercial platinum-carbon catalyst Tafel curve and CV comparison curve.

[0037] Fig.12 It is the overpotential distribution diagram of the catalyst prepared after doping each sample.

[0038] Fig.13 The effect of sodium borohydride addition method on electrode performance. DETAILED DESCRIPTION

[0039] The preparation method of the present invention is described in detail as follows:

[0040] First, prepare the perovskite material BaZr 0.1 Ce 0.7 Y 0.2 O 3-σ . Dissolve zirconium nitrate, barium nitrate, cerium nitrate and yttrium nitrate in deionized water at a certain molar ratio, then add ethylenediaminetetraacetic acid and citric acid, add a small amount of ammonia water to adjust the pH of the solution to neutral, stir to dry at 100°C, then dry in an oven at 180°C overnight and collect. The collected powder was calcined at 1000-1200°C for 10h to obtain perovskite BZCY; 60mg of the calcined powder and 60mg of high specific surface area carbon EC-600JD were dispersed in ethylene glycol, ultrasonicated, stirred and dried to obtain a mixed substrate.

[0041] 100 mg of the composite carrier obtained in the previous step and 66.6 mg of the ruthenium source were dispersed in ethylene glycol to form a ruthenium precursor solution, and then 0.15 g of sodium borohydride was slowly added to the ethylene glycol and stirred to obtain a ruthenium precursor solution containing Na + The ethylene glycol solution of B-(OCH2CH2OH)4 is slowly added dropwise to the ruthenium precursor solution, and stirred continuously at 40°C-50°C for 8 hours to reduce the nanoscale ruthenium in situ and load it on the mixed substrate. Finally, the product is washed with a large amount of deionized water, filtered, and vacuum dried overnight to obtain a catalyst uniformly loaded with ruthenium nanoparticles.

[0042] In the above steps, the molar ratio of zirconium nitrate, barium nitrate, cerium nitrate and yttrium nitrate is: 0.1-0.2:1:0.6-0.8:0.1-0.3; the ruthenium source is ruthenium trichloride (RuCl3·xH2O); the mass ratio of perovskite BZCY and high specific surface area carbon EC-600JD is 1:1. In the above preparation method, the perovskite BZCY is successfully incorporated into the carbon substrate. The proton conductivity of BZCY improves the proton conduction process in the hydrogen evolution reaction. At the same time, the trace metal ions precipitated during the preparation of the perovskite modify the ruthenium doping of the main active site, thereby improving the activity of the catalyst; at the same time, the doping of the perovskite can inhibit the agglomeration of metal particles on the substrate surface, improve the interaction between the metal and the carrier, reduce the impact of carbon corrosion, and improve the durability of the proton exchange membrane water electrolysis hydrogen production under actual hydrogen production conditions.

[0043] Example 1

[0044] 2.6134g Ba(NO3)2, 0.4293g Zr(NO3)4·5H2O, 3.0395g Ce(NO3)3·6H2O, 0.7660g Y(NO3)3·6H2O were dissolved in deionized water, and then 0.02mol ethylenediaminetetraacetic acid and 0.04mol citric acid were added, and a small amount of ammonia was added to adjust the pH to neutral, and then stirred at 100°C, and finally dried in an oven at 180°C overnight and collected. The dried powder was calcined at 1000°C in air for 10 hours to obtain the sample BaZr 0.1 Ce 0.7 Y 0.2 O 3-σ (hereinafter referred to as BZCY); 60 mg of the calcined powder and 60 mg of high specific surface area carbon EC-600JD were dispersed in ethylene glycol, ultrasonicated, stirred and dried to obtain a mixed substrate (hereinafter referred to as BZCY-C). 100 mg of the composite carrier and 66.6 mg of the ruthenium source were dissolved in ethylene glycol to form a ruthenium precursor solution, and then 0.15 g of sodium borohydride was slowly added to the ethylene glycol and stirred to obtain a ruthenium precursor solution containing Na + B - The ethylene glycol solution of (OCH2CH2OH)4 was slowly added dropwise to the ruthenium precursor solution and stirred continuously at 40°C for 8 hours to reduce the nanoscale ruthenium in situ and load it on the mixed substrate. Finally, the product was washed with a large amount of deionized water, filtered, and dried in vacuum overnight to obtain a catalyst uniformly loaded with ruthenium nanoparticles.

[0045] The schematic diagram of the interlayer experiment of the prepared catalyst is shown in Figure 1As shown in the A area, EC-600JD, BZCY and BZCY-C were sprayed as interlayers between two Nafion membranes using the traditional CCM method to prepare membrane electrodes, and their performance was tested under a standard proton exchange membrane fuel cell system. The principle of power generation in proton exchange membrane fuel cells is that hydrogen oxidation occurs at the anode to produce protons, which are conducted to the cathode through the proton exchange membrane in the middle to undergo an oxygen reduction reaction. Then, electrons pass through an external circuit to generate a potential difference and generate electricity. If there are no protons from the anode to the cathode, the membrane electrode will have no performance. Therefore, the use of this interlayer experimental analysis of performance can prove whether the interlayer material can conduct protons. Figure 1 In the B area, it can be seen that the peak power of the membrane electrode without interlayer is 303mW / cm 2 , pure carbon (EC-600JD) interlayer has almost no performance, BaZr 0.1 Ce 0.7 Y 0.2 O 3-σ (BZCY) for interlayer is 117mW / cm 2 , BZCY-C is 76mW / cm 2 From the peak power comparison, it can be seen that pure carbon has almost no ability to conduct protons, while BZCY has the ability to conduct protons, and its doping into carbon can enhance the ability of the substrate to conduct protons. Figure 1 Area C is the cross-sectional SEM image of the membrane electrode in the sandwich experiment. It can be seen that during the preparation process of the sandwich membrane electrode, the Nafion membranes on both sides are well isolated by the middle interlayer and there is no adhesion phenomenon, which further proves the feasibility and rigor of the experiment.

[0046] like Figure 2 As shown in the SEM image of area A, BZCY-C particles are uniform in size and distribution. Figure 2 In the TEM image in area B, Ru particles are uniformly loaded on the surface of the mixed substrate, with an average size between 3-5 nm. Figure 2 The C and D regions of the image show the lattice micrographs of Ru particles. After analysis, the lattice spacings of Ru were obtained, which were 0.242nm, 0.205nm and 0.215nm, respectively, corresponding to the (100), (101) and (002) crystal planes of Ru. Compared with the standard lattice spacing of Ru, the measured lattice spacing has become larger, and lattice stretching has occurred, indicating that elements with larger atomic radius than Ru have been doped into the Ru lattice. Figure 2From the EELS spectrum of the E region, we can see that the characteristic peaks of Ba and Ce are detected on a single Ru particle, indicating that Ba and Ce are doped into the Ru particle. This is mainly because the introduction of the reducing agent can reduce and precipitate with the metal in the perovskite material, and then enter the Ru lattice, which proves that the increase in lattice spacing is due to the doping of Ba and Ce. The tensile stress generated by lattice stretching can regulate the Ru to H + and OH - The adsorption of oxygen-containing intermediates can greatly improve the hydrogen evolution activity of the catalyst.

[0047] Figure 3 From the XRD diagram of area A, it can be seen that the phase structure of BZCY has hardly changed after Ru is loaded, retaining the complete perovskite structure, except for an additional characteristic peak of Ru at the 44° position, indicating that Ru is well loaded on it. Figure 3 The XPS image of region B shows that the Ru loaded on it is in a metallic state and its valence state has not changed due to the doping of BZCY. The metallic Ru is the valence state with the highest hydrogen evolution activity among the valence states of Ru. The binding energies of the two characteristic peaks of Ru are 462.73 eV and 484.87 eV, respectively, which are higher than the binding energies of standard Ru (462.1 eV and 484.1 eV). This indicates that there is electron transfer between Ru and the doping elements and the oxide substrate, and the resulting electron interaction is beneficial to regulating the electronic structure, thereby improving activity and stability.

[0048] Figure 4 This is the LSV comparison curve of Ru-BZCY-C and commercial platinum carbon. In the figure, Ru-BZCY-C and Pt / C are at 10mA / cm 2 The overpotentials are 18 mV and 20.3 mV respectively. The overpotential of the sample is less than that of Pt / C, indicating that this sample has better hydrogen evolution reaction activity.

[0049] Figure 5 The performance curve of the water electrolysis hydrogen production device prepared by using Ru-BZCY-C and Pt / C as cathode and IrO2 as anode. The electrolyzer uses standard all-alloy components with an active area of ​​4cm 2The cathode and anode catalyst slurries are made of Ru-BZCY-C, Pt / C and IrO2 as powders, with isopropanol and Nafion (5wt%) solution ultrasonically mixed and prepared, and the I / C is 0.416 (ratio of ionomer to carbon). The water-dissolving membrane electrode is prepared by a five-in-one hot pressing method, which consists of a Nafion membrane sprayed with catalyst on both sides, edge guards on both sides and carbon paper on the outermost sides. In the test, pure water was used as the electrolyte and continuously circulated in the device. The test procedure was to use a standard water electrolysis system to perform an I / V curve test in the voltage range of 1V-2.5V. From the curve, it can be seen that Ru-BZCY-C only needs 1.65V to reach 2A / cm 2 The current density of Ru-BZCY-C is 2.20 V, while Pt / C needs 2.20 V to reach this current density, indicating that Ru-BZCY-C has a better hydrogen production effect as a cathode in practical applications.

[0050] Figure 6 This is the curve before and after the electrochemical stability test of Ru-BZCY-C and Pt / C. The accelerated durability test is a test to observe the durability of the catalyst. The test temperature is 25°C, the test environment is 0.1M HClO4 saturated with argon, the counter electrode used is a carbon rod, and the reference electrode is Ag / AgCl. Cycle in the scanning range of -0.6V-0V. After the cycle, the LSV test is performed to obtain the performance after the durability test, and the initial performance is compared to obtain the degree of performance attenuation. After 50,000 cycles of accelerated durability cycle testing, the performance of Ru-BZCY-C has hardly changed, while the overpotential of Pt / C has increased by 30mV, indicating that after BZCY doping, the durability of the catalyst has been greatly improved.

[0051] Figure 7 This is the TEM image of Ru-BZCY-C after undergoing 50,000 cycles of accelerated durability cycle test. It can be clearly seen that although the Ru particles are aggregated together after the long-term stability test, there is no agglomeration between the particles, they are still evenly dispersed, and the particle size has not increased significantly, proving that the sample has good stability.

[0052] Example 2

[0053] 2.6134g Ba(NO3)2, 0.4293g Zr(NO3)4·5H2O, 3.4737g Ce(NO3)3·6H2O, 0.3830g Y(NO3)3·6H2O were dissolved in deionized water, and then 0.02mol ethylenediaminetetraacetic acid and 0.04mol citric acid were added, and a small amount of ammonia was added to adjust the pH to neutral, and then stirred at 100°C, and finally dried in an oven at 180°C overnight and collected. The dried powder was calcined at 1000°C in air for 10 hours to obtain the sample BaZr 0.1 Ce0.7 Y 0.2 O 3-σ ; Disperse 60 mg of the calcined powder and 60 mg of high specific surface area carbon EC-600JD in ethylene glycol, ultrasonicate, stir and dry to obtain a mixed substrate. Dissolve 100 mg of the composite carrier and 66.6 mg of the ruthenium source in ethylene glycol to form a ruthenium precursor solution, then slowly add 0.15 g of sodium borohydride to the ethylene glycol and stir to obtain a ruthenium precursor solution containing Na + B - The ethylene glycol solution of (OCH2CH2OH)4 was slowly added dropwise to the ruthenium precursor solution and stirred continuously at 50°C for 8 hours to reduce the nanoscale ruthenium in situ and load it on the mixed substrate. Finally, the product was washed with a large amount of deionized water, filtered, and dried in vacuum overnight to obtain a catalyst uniformly loaded with ruthenium nanoparticles. Figure 8 It is Ru-BaZr 0.1 Ce 0.8 Y 0.1 O 3-σ -C (BZCY-Ru-C) and commercial platinum carbon catalyst LSV performance comparison curve, from the figure can be seen that BZCY-Ru-C at 10mA / cm 2 The overpotential under the condition of Ru is slightly smaller than that of Pt / C. Ru has a lower cost than Pt, and the Ru content in the sample is also very small, only 8wt% (the result is accurately measured by an inductively coupled plasma spectrometer), which shows that the sample has a good prospect for industrial application.

[0054] Example 3

[0055] 2.6134g Ba(NO3)2, 0.8586g Zr(NO3)4·5H2O, 3.0395g Ce(NO3)3·6H2O, 0.3830g Y(NO3)3·6H2O were dissolved in deionized water, and then 0.02mol ethylenediaminetetraacetic acid and 0.04mol citric acid were added, and a small amount of ammonia was added to adjust the pH to neutral, and then stirred at 100°C, and finally dried in an oven at 180°C overnight and collected. The dried powder was calcined at 1100°C in air for 10 hours to obtain the sample BaZr 0.1 Ce 0.7 Y 0.2 O 3-σ ; Disperse 60 mg of the calcined powder and 60 mg of high specific surface area carbon EC-600JD in ethylene glycol, ultrasonicate, stir and dry to obtain a mixed substrate. Dissolve 100 mg of the composite carrier and 66.6 mg of the ruthenium source in ethylene glycol to form a ruthenium precursor solution, then slowly add 0.15 g of sodium borohydride to the ethylene glycol and stir to obtain a ruthenium precursor solution containing Na + B -(OCH2CH2OH)4 ethylene glycol solution, slowly add the solution to the ruthenium precursor solution, and continue stirring at 40°C for 8 hours to reduce the nano-scale ruthenium in situ and load it on the mixed substrate. Finally, the product is washed with a large amount of deionized water, filtered, and vacuum dried overnight to obtain a catalyst uniformly loaded with ruthenium nanoparticles. Compared with traditional carbon substrates, oxides can well avoid the influence of carbon corrosion in catalyst testing. Fig. 9 It can be analyzed from the comparison of the constant current stability test curves in Ru-BaZr 0.2 Ce 0.7 Y 0.1 O 3-σ -C(BZCY-Ru-C) at 10mA / cm 2 After running stably for 120h, the performance of Pt / C was almost unchanged at 10mA / cm 2 After running for 120 hours, the overpotential increased by 26 mV, indicating that the BZCY doping in this patent greatly improves the stability of the main active site Ru and enables long-term stable operation.

[0056] Example 4

[0057] 2.6134g Ba(NO3)2, 0.8586g Zr(NO3)4·5H2O, 2.6053g Ce(NO3)3·6H2O, 0.7660g Y(NO3)3·6H2O were dissolved in deionized water, and then 0.02mol ethylenediaminetetraacetic acid and 0.04mol citric acid were added, and a small amount of ammonia was added to adjust the pH to neutral, and then stirred at 100°C, and finally dried in an oven at 180°C overnight and collected. The dried powder was calcined at 1000°C in air for 10 hours to obtain the sample BaZr 0.1 Ce 0.7 Y 0.2 O 3-σ ; Disperse 60 mg of the calcined powder and 60 mg of high specific surface area carbon EC-600JD in ethylene glycol, ultrasonicate, stir and dry to obtain a mixed substrate. Dissolve 100 mg of the composite carrier and 66.6 mg of the ruthenium source in ethylene glycol to form a ruthenium precursor solution, then slowly add 0.15 g of sodium borohydride to the ethylene glycol and stir to obtain a ruthenium precursor solution containing Na + B - The ethylene glycol solution of (OCH2CH2OH)4 was slowly added dropwise to the ruthenium precursor solution and stirred continuously at 40°C for 8 hours to reduce the nanoscale ruthenium in situ and load it on the mixed substrate. Finally, the product was washed with a large amount of deionized water, filtered, and dried in vacuum overnight to obtain a catalyst uniformly loaded with ruthenium nanoparticles. Fig.10 It is Ru-BaZr 0.2 Ce 0.6Y 0.2 O 3-σ -C (BZCY-Ru-C) and commercial platinum carbon catalyst electrolysis water hydrogen production device stability comparison curve. As can be seen from the figure, when BZCY-Ru-C and platinum carbon are used as cathodes for hydrogen production in water electrolysis devices, at 2A / cm 2 In the stability test of running under the current density for 100 hours, the attenuation can be maintained at a small level, ensuring the small fluctuation of hydrogen production under working conditions. However, BZCY-Ru-C can achieve long-term stable operation at a high current density with a lower voltage, which has great industrial application value.

[0058] Example 5

[0059] 2.6134g Ba(NO3)2, 0.4293g Zr(NO3)4·5H2O, 2.6053g Ce(NO3)3·6H2O, 1.1490g Y(NO3)3·6H2O were dissolved in deionized water, and then 0.02mol ethylenediaminetetraacetic acid and 0.04mol citric acid were added, and a small amount of ammonia water was added to adjust the pH to neutral, and then stirred at 100°C, and finally dried in an oven at 180°C overnight and collected. The dried powder was calcined at 1000°C in air for 10 hours to obtain the sample BaZr 0.1 Ce 0.7 Y 0.2 O 3-σ ; Disperse 60 mg of the calcined powder and 60 mg of high specific surface area carbon EC-600JD in ethylene glycol, ultrasonicate, stir and dry to obtain a mixed substrate. Dissolve 100 mg of the composite carrier and 66.6 mg of the ruthenium source in ethylene glycol to form a ruthenium precursor solution, then slowly add 0.15 g of sodium borohydride to the ethylene glycol and stir to obtain a ruthenium precursor solution containing Na + The ethylene glycol solution of B-(OCH2CH2OH)4 was slowly added dropwise to the ruthenium precursor solution and stirred continuously at 40°C for 8 hours to reduce the nanoscale ruthenium in situ and load it on the mixed substrate. Finally, the product was washed with a large amount of deionized water, filtered, and dried in vacuum overnight to obtain a catalyst uniformly loaded with ruthenium nanoparticles. Fig.11 It is Ru-BaZr 0.1 Ce 0.6 Y 0.3 O 3-σ -C(BZCY-Ru-C) and commercial platinum-carbon catalyst Tafel curve and CV comparison curve. Fig.11It can be analyzed that the Tafel values ​​of BZCY-Ru-C and Pt / C are 29mV / dec and 34mV / dec respectively. The smaller Tafel values ​​indicate that the samples prepared by this patent have faster reaction kinetics, which is due to the fact that BZCY accelerates the most important rate-controlling step of hydrogen proton transfer in the hydrogen evolution reaction. The Cdl values ​​of BZCY-Ru-C and Pt / C are 18.2mF / cm 2 and 14.6mF / cm 2 The Cdl value is directly proportional to the electrochemically active area. A larger Cdl value represents a larger electrochemically active area, indicating that the sample prepared by this patent has a better electrochemically active area. A larger electrochemically active area means that more active sites on the surface are exposed, representing better catalytic activity.

[0060] Comparative experiment 1

[0061] Compared with Example 1, the same preparation steps were used to prepare other similar perovskite materials and oxide materials as comparative samples, and the same method was used to load Ru on pure carbon (C) as a comparative sample. The preparation method is as follows: Referring to Example 1, 60 mg of high specific surface area carbon EC-600JD was dispersed in ethylene glycol, ultrasonicated, stirred and then dried to obtain a carrier. 100 mg of the carrier and 66.6 mg of the ruthenium source were dissolved in ethylene glycol to form a ruthenium precursor solution, and then 0.15 g of sodium borohydride was slowly added to the ethylene glycol, and stirred to obtain a solution containing Na + The ethylene glycol solution of B-(OCH2CH2OH)4 is slowly added dropwise to the ruthenium precursor solution, and stirred continuously at 40°C for 8 hours to reduce the nanoscale ruthenium in situ and load it on the carrier. Finally, the product is washed with a large amount of deionized water, filtered, and dried in vacuum overnight to obtain a catalyst uniformly loaded with ruthenium nanoparticles, hereinafter referred to as C+Ru.

[0062] In addition, other oxide materials were used to conduct electrolytic hydrogen decomposition experiments. In the experiments, the following oxides were used to replace BZCY in the above examples, and the catalysts were prepared and tested for performance in the same manner. The catalysts here include:

[0063] SqF 0.2 Nb 0.3 Co 0.3 Fe 0.2 O 3-σ (SSNCF), Ba 0.8 Sr 0.2 Co 0.5 Fe 0.5 O 3-σ (BSCF), BaCo 0.2 Fe 0.3 Zr 0.3 Y0.2 O 3-σ (BCFZY), SrTi 0.5 Fe 0.5 O 3-σ (STF), YSZ (yttrium-doped cerium oxide), Ce 0.9 G 0.1 O 1.95 (GDC), SDC (Samarium doped cerium oxide). In the experiment, the same preparation and performance characterization methods were used, and the test results obtained are as follows:

[0064] Fig.12 This is the overpotential distribution diagram of the catalyst prepared after doping each sample. It can be seen from the figure that the overpotential after doping with BZCY is the lowest, showing the best hydrogen evolution reaction performance. In contrast, when C+Ru material is directly used, the overpotential is significantly higher than that after doping with BZCY, indicating that the activity of the hydrogen evolution reaction is significantly worse than that after doping with BZCY. The doping of BZCY can improve the proton conductivity of the substrate itself. In the hydrogen evolution reaction, the proton conduction step is the key rate-controlling step. The improvement of the proton capacity of the substrate can well transfer protons to the surface of the main active site Ru on the surface, promoting the conversion of protons to hydrogen; at the same time, a small amount of internal transition metals are precipitated and doped into Ru during the doping process of BZCY, which adjusts the electronic structure of Ru itself and optimizes the hydrogen evolution reaction activity of Ru. This comparison clearly reflects that BZCY doping has greatly improved the overall catalyst.

[0065] The relevant specific performance values ​​are summarized and compared with the catalyst performance reported in previous literature as shown in the following table:

[0066]

[0067]

[0068] The difference between comparative experiment 2 and example 1 is that the reducing agent is added in a different way. Sodium borohydride is directly and slowly added to the ruthenium precursor solution, and the other parameters are the same, and the same test is performed.

[0069] The direct reduction reaction of sodium borohydride (NaBH4) powder added to ethylene glycol is violent, and the reduced particles are large in size and easily agglomerated on the substrate surface, such as Fig.13 As shown on the right side of the graph, Ru particles aggregate on the mixed substrate, which greatly affects the activity of the hydrogen evolution reaction. Sodium borohydride is first dissolved in ethylene glycol, and the Na +B-(OCH2CH2OH)4 is both a reducing agent and a stabilizer. By adding the reducing solution dropwise into an ethylene glycol solution containing a ruthenium source, the ruthenium ions can be slowly reduced to ruthenium nanoparticles at a certain temperature and loaded evenly and stably on the substrate, thus avoiding the problem of large particles and agglomeration caused by overly violent reactions. Fig.13 The left side is the LSV performance comparison curve of two different reduction methods. The overpotential of direct addition is 30.3mV, which is higher than that of Na + The overpotential of the reduction of B-(OCH2CH2OH)4 solution increased by 10mV, indicating that the reduction method of this patent is better.

Claims

1. An oxide-doped hydrogen evolution electrocatalyst, characterized in that: The invention comprises a substrate and Ru nanoparticles loaded on the substrate; the substrate is a mixture of carbon particles and perovskite oxide, and the perovskite oxide is selected from BaZr 0.1+ x Ce 0.8-x-y Y 0.1+y O 3-σ , and the Ru nanoparticles are also doped with metal elements Ba and Ce, 0.1≤x, y≤0.1; the perovskite oxide is selected from SrSc 0.2 Nb 0.3 Co 0.3 Fe 0.2 O 3-σ , Ba 0.8 Sr 0.2 Co 0.5 Fe 0.5 O 3-σ ,BaCo 0.2 Fe 0.3 Zr 0.3 Y 0.2 O 3-σ 、SrTi 0.5 Fe 0.5 O 3-σ One of; The preparation method of the oxide-doped hydrogen evolution electrocatalyst comprises the following steps: Step 1, mixing perovskite oxide and carbon particles and dispersing them in a first solvent, and drying them to obtain a composite carrier; Step 2, dissolving the composite carrier and the ruthenium source in a second solvent, adding a reducing agent to carry out a reduction reaction so that the ruthenium is loaded on the composite carrier, and the product is separated and dried to obtain a catalyst; In the step 1, the weight ratio of perovskite oxide to carbon particles is 1:0.5-1.5; and the reducing agent is sodium borohydride.

2. The oxide-doped hydrogen evolution electrocatalyst according to claim 1, characterized in that: The particle size of the Ru nanoparticles is 3-5 nm.

3. The oxide-doped hydrogen evolution electrocatalyst according to claim 1, characterized in that: Perovskite oxides are prepared by a sol-gel method.

4. The oxide-doped hydrogen evolution electrocatalyst according to claim 1, characterized in that: In the step 2, the reducing agent is first dispersed in the second solvent and then slowly added to carry out the reduction reaction.

5. The oxide-doped hydrogen evolution electrocatalyst according to claim 1, characterized in that: In the step 2, the weight ratio of the composite carrier, the ruthenium source and the reducing agent is 1:0.5-1.5:1-3.

6. The oxide-doped hydrogen evolution electrocatalyst according to claim 1, characterized in that: In the step 2, the reaction conditions are 20-60° for 5-15h.

7. Use of the oxide-doped hydrogen evolution electrocatalyst according to claim 1 in hydrogen production by proton exchange membrane water electrolysis.

Citation Information

Patent Citations

  • Supported metal ruthenium catalyst, and preparation method and application thereof

    CN110833846A

  • Fuel cell electrocatalyst and preparation method thereof

    CN113611886A

Cited By

  • Partially non-crystallized oxide doped hydrogen evolution electrocatalyst and preparation method and application thereof

    CN122214926A